The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1103/physrevb.76.245123
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductance in duplex DNA: Helical effects and low-frequency vibrational coupling

Abstract: In this work we consider the combined effect of helical structure and base-pair twist motion on charge transfer through duplex DNA at low temperatures. We present a fully analytical treatment of charge-lattice coupled dynamics in terms of nearest-neighbor tight-binding equations describing the propagation of the charge through an effective linear lattice for certain frequency values. The corresponding effective hopping terms include both helicoidal and dynamical effects in a unified way. Although base-pair mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
(68 reference statements)
2
27
0
Order By: Relevance
“…31 Subsequently, the combined effect of helical structure and bps twist motion on charge transfer through more realistic duplex DNA at low temperatures was considered. 32 The physical picture emerging from that work was that although an ensemble of bps twisting back and forth around the helix axis generally results in a degraded charge-transfer efficiency, a significant improvement of charge migration can occur via charge coupling to certain lattice modes at low temperatures, in line with several works suggesting that structural fluctuations may facilitate charge transfer in DNA. 9,33,34 In fact, recent quantum-mechanics/ molecular-dynamics studies of a duplex ͑GT͒ 15 oligomer have shown the presence of large fluctuations of t 2 ͑the magnitude determining the charge-transfer rate͒ about one order of magnitude larger than the averaged ͗t 2 ͘ value, occurring every 1 ps on the average.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…31 Subsequently, the combined effect of helical structure and bps twist motion on charge transfer through more realistic duplex DNA at low temperatures was considered. 32 The physical picture emerging from that work was that although an ensemble of bps twisting back and forth around the helix axis generally results in a degraded charge-transfer efficiency, a significant improvement of charge migration can occur via charge coupling to certain lattice modes at low temperatures, in line with several works suggesting that structural fluctuations may facilitate charge transfer in DNA. 9,33,34 In fact, recent quantum-mechanics/ molecular-dynamics studies of a duplex ͑GT͒ 15 oligomer have shown the presence of large fluctuations of t 2 ͑the magnitude determining the charge-transfer rate͒ about one order of magnitude larger than the averaged ͗t 2 ͘ value, occurring every 1 ps on the average.…”
Section: Introductionsupporting
confidence: 63%
“…Thus, effective model Hamiltonians can be expressed as the sum of two main contributions H = H e + H l , where H e describes the charge dynamics over the -stacked electronic system and H l describes the duplex DNA dynamics. The electronic degrees of freedom of a double-stranded DNA ͑including sugar-phosphate and environmental effects͒ are described in terms of the effective Hamiltonian, 32,42,43 …”
Section: Dna Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, carrier coupling to low-frequency vibrational modes may give rise to a significant improvement of the conductance. 15 Recent experiments in poly͑G͒-poly͑C͒ and poly͑A͒-poly͑T͒ DNA molecules in solution suggest that they may act as nanowires supporting high electrical current under moderate bias. 9 The nucleotide sequence in synthetic poly͑G͒-poly͑C͒ and poly͑A͒-poly͑T͒ DNA molecules is periodic.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the effective model Hamiltonian can be expressed as the sum of two main contributions H ¼ H e þ H l , where H e describes the charge carrier dynamics over the p-stacked electronic system and H l describes the duplex DNA dynamics. The electronic degrees of freedom of a double-stranded DNA (including sugar-phosphate and environmental effects) are described in terms of the effective Hamiltonian [23],…”
Section: Helical Geometry and Dynamical Effectsmentioning
confidence: 99%